Enhancing students' learning journey through artificial intelligence and a packaged educational platform - Winarko, Ricky (Nanyang Technological University, 2024)
Recent years have been quite eventful in the field of Artificial Intelligence (AI) with the advent of Large Language Models (LLMs). This bourgeoning technology has unlocked a world of potentials when it comes to information synthesis and retrieval. These powerful features can improve the learning experience of students by utilizing dialogic pedagogy to spur the creative process and improve disciplinary competence. Through this report, I will discuss how LLMs can improve the education quality of students overall, as well as implementation of this feature onto a packaged online platform that empower teachers in improving the student’s classroom experience.